2019
DOI: 10.1002/ppap.201900191
|View full text |Cite
|
Sign up to set email alerts
|

An atmospheric pressure non‐self‐sustained glow discharge in between metal/metal and metal/liquid electrodes

Abstract: Non-thermal plasmas operating at high pressure attract increasing attention for a variety of applications as an alternative to conventional chemical processes.In this study, an atmospheric pressure direct current non-self-sustained discharge in nitrogen is investigated as a source of non-thermal plasma capable of operating in a glow regime. The discharge is sustained between an internal source of ionization and a metal or liquid electrode and studied by electrical diagnostics as well as by spectroscopy methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…25,26 On the other hand, the evaluation of the vibrational temperature of probe-excited molecules is often useful to verify the nonequilibrium behavior of the plasma. 27 The vibrational excitation indicates the efficiency of the energy exchange between free electrons and molecules. Indeed, several molecules, such as N 2 and O 2 , are available in the ambient air surrounding the plasma jet and are vibrationally excited through electron impacts.…”
Section: Methodsmentioning
confidence: 99%
“…25,26 On the other hand, the evaluation of the vibrational temperature of probe-excited molecules is often useful to verify the nonequilibrium behavior of the plasma. 27 The vibrational excitation indicates the efficiency of the energy exchange between free electrons and molecules. Indeed, several molecules, such as N 2 and O 2 , are available in the ambient air surrounding the plasma jet and are vibrationally excited through electron impacts.…”
Section: Methodsmentioning
confidence: 99%
“…39 At the same time, T gas measured using the OH(A) rotational structure is ∼1000 K higher than T gas obtained from N 2 (C) rotational bands. Sremački et al 40 showed a non-uniform emission signal distribution along the plasma column, indicating that the highest emission signal from OH(A) rotational bands was observed close to the liquid electrode. This means that in our case, although the emission signals were space averaged, the temperatures determined using OH(A) rotational bands can be prescribed to the region with a high OH radicals concentration, i.e., close to the surface of the liquid, while the N 2 (C) ro-vibrational transition determines the temperature closer to the pin (top-electrode in Fig.…”
Section: Insights Into Plasmas With and Without Watermentioning
confidence: 99%
“…In addition, T vib of the PL system is ∼500 K lower than that of the PP configuration, suggesting a lower vibrational excitation of N 2 due to an effective quenching of these states by H 2 O as indicated in previous works. 40,41 The effect of air flow on the temperatures is investigated at 1, 2, and 3 slm. Both T gas and T vib remain constant when varying the gas flow as shown in the ESI, Fig.…”
Section: Insights Into Plasmas With and Without Watermentioning
confidence: 99%
See 1 more Smart Citation
“…In non-thermal plasmas, the translational-rotational equilibrium is not always achieved, and the gas temperature may differ from the rotational one [28,29]. Therefore, in this work, gas temperature was directly measured using time-resolved Rayleigh scattering spectroscopy.…”
Section: Gas Temperature Measurementsmentioning
confidence: 99%